Gerakan Transnasional dan Kebijakan : Strategi Advokasi Greenpeace Detox Campaign on Fashion di Tiongkok - Puti Parameswari (Dauliyah Journal of Islamic and International Affairs, 2016)
This study aims to understand the power of NGOs through advocacy campaign strategies to change the behavior or policies of other actors. This study analyzed Greenpeace advocacy on Detox Campaign on Fashion in China, in the period of 2011 to 2013. The main advocacy strategies used by Greenpeace is campaign—include information politics, leverage politics, symbolic politics and accountability politics. This research also analyzed the relations between Greenpeace as NGO and targeted actors, namely global brand fashion, global society and state actors, China. This study found that the campaign strategy success in influencing targeted actors to change their behavior and policies regard to the issue of water pollution in China.